2021
DOI: 10.1111/1759-7714.13825
|View full text |Cite
|
Sign up to set email alerts
|

Crizotinib for recurring non‐small‐cell lung cancer with EML4‐ALK fusion genes previously treated with alectinib: A phase II trial

Abstract: Background The efficacy of crizotinib treatment for recurring EML4‐ALK‐positive non‐small cell lung cancer (NSCLC) previously treated with alectinib is unclear. Based on our preclinical findings regarding hepatocyte growth factor/mesenchymal epithelial transition (MET) pathway activation as a potential mechanism of acquired resistance to alectinib, we conducted a phase II trial of the anaplastic lymphoma kinase/MET inhibitor, crizotinib, in patients with alectinib‐refractory, EML4‐ALK‐positive NSCLC. Methods P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…After oral administration of crizotinib for 7 days, there was an increase in the levels of ALT and AST, indicating that the liver may have suffered some degree of damage. This is consistent with previous reports ( Harada et al, 2021 ; Tsukita et al, 2015 ).…”
Section: Discussionsupporting
confidence: 94%
“…After oral administration of crizotinib for 7 days, there was an increase in the levels of ALT and AST, indicating that the liver may have suffered some degree of damage. This is consistent with previous reports ( Harada et al, 2021 ; Tsukita et al, 2015 ).…”
Section: Discussionsupporting
confidence: 94%
“…Indeed, a result of phase II trial showed limited efficacy of crizotinib to patients with ALK‐positive NSCLC treated with alectinib immediately before crizotinib monotherapy. 54 In our study, cMET activation was observed in JFCR‐059‐2 and was found to induce EGFR and HER3 tyrosine phosphorylation, as previously reported in MET amplification–mediated EGFR‐TKI gefitinib resistance. 55 However, in JFCR‐059‐2 cells, combination of alectinib or lorlatinib with crizotinib (as a cMET inhibitor) could induce almost complete eradication of tumor in an in vivo model.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, these reports suggest that crizotinib cannot completely overcome this resistance despite its ability to inhibit cMET activation. Indeed, a result of phase II trial showed limited efficacy of crizotinib to patients with ALK‐positive NSCLC treated with alectinib immediately before crizotinib monotherapy 54 . In our study, cMET activation was observed in JFCR‐059‐2 and was found to induce EGFR and HER3 tyrosine phosphorylation, as previously reported in MET amplification–mediated EGFR‐TKI gefitinib resistance 55 .…”
Section: Discussionsupporting
confidence: 82%
“…MET gene amplification has previously been described as a bypass resistance mechanism to TKIs, first discovered in EGFR mutant NSCLC resistant to gefitinib 47 and subsequently observed in ALK rearranged and RET rearranged NSCLC 26,48–55 . More recently, MET gene amplification has been observed in ROS1+ lung cancers that progressed on lorlatinib, a next‐generation ROS1 TKI utilized to target some ROS1 mutations driven by first‐generation ROS1 TKIs 22 .…”
Section: Discussionmentioning
confidence: 99%
“…MET gene amplification has previously been described as a bypass resistance mechanism to TKIs, first discovered in EGFR mutant NSCLC resistant to gefitinib 47 and subsequently observed in ALK rearranged and RET rearranged NSCLC. 26 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 More recently, MET gene amplification has been observed in ROS1+ lung cancers that progressed on lorlatinib, a next‐generation ROS1 TKI utilized to target some ROS1 mutations driven by first‐generation ROS1 TKIs. 22 To our knowledge, this represents the first case of MET‐mediated resistance to entrectinib in ROS1+ NSCLC, and importantly shows a novel mechanism involving ecDNA MET gene amplification.…”
Section: Discussionmentioning
confidence: 99%